GAMBARAN IKLIM KESELAMATAN KONSTRUKSI DI PROYEK A DKI JAKARTA - Huzain, Mohamad Reza; Lestari, Fatma (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Construction is one sector that has a high complexity and has a rapid development every year. It can be said that the construction sector is an industry that has a high risk. The contribution of accidents in the construction sector is mostly caused by unsafe behavior even though there are already ongoing safety programs. A safety climate can increase worker safety awareness and reduce unsafe work behavior. This study aims to describe the profile of the safety climate in project A as one of the pilot construction projects in DKI Jakarta. The sample in this study were workers in project A totaling 272 workers whose data were taken through a questionnaire using the cross-sectional method. The results of this study explain that the safety climate in project A is at a proactive level where the scores for the variables safety as value, leadership, empowerment, and communication have the highest numbers and the variables commitment, accountability and training at all levels have less numbers and need attention from organization. Program implementation and commitment from management are the focus of project A to improve the safety climate in project A